Baduy Traditional Medicine and Modern Medicalization: Spirituality as an Alternative Health Knowledge System - Rahmat Ikhsanudin; Milla Sukra; Febrian Alfiana; Mukhayah Tiarawati (Yayasan Albahriah Jamiah Indonesia, 2026)
The dominance of the biomedical paradigm in the formal health system tends to marginalize indigenous health practices as irrational, despite their recognized effectiveness in certain socio-cultural contexts. However, studies on the epistemological structure of Baduy indigenous medicine and its relationship to modern medicalization are still limited. This study aims to analyze the knowledge system of Baduy indigenous medicine and identify the dynamics of its interaction with the modern health system. This study uses a qualitative approach based on critical ethnography, drawing on a systematic literature review of scientific publications, ethnographic reports, and related documents, which are analyzed using interpretive thematic analysis to uncover patterns of health knowledge, practices, and discourses. Baduy indigenous medicine has a coherent epistemological structure that integrates spirituality, cosmology, and ecological relations as the basis for diagnosis, therapy, and disease prevention. Diagnosis is carried out through reading bodily signs and imbalances in the human-nature relationship. At the same time, therapy includes healing rituals, the use of herbal remedies, and behavioral regulation based on customary norms. Spirituality serves as an operational framework that regulates health practices systemically, not merely symbolically. The analysis also reveals three patterns of relationships with modern medicalization: selective resistance to interventions perceived as disruptive to the customary order; pragmatic adaptation in specific cases, such as infectious diseases; and functional coexistence without full integration. These findings confirm that Baduy traditional medicine is a legitimate alternative health knowledge system and demonstrate the importance of recognizing medical pluralism in developing inclusive health policies.